The impact of whistleblowing in reducing corruption in the private sector - Mayekiso, Christopher Melumzi (Rhodes University, 2026)
The research investigated the impact of whistleblowing in reducing corruption in the private sector. In addition to determining whistleblowing's impact in reducing corruption in the private sector, the study also aimed to examine barriers faced by potential whistleblowers and analyse whistleblowing's moral motivation and impact on organisational reputation and stakeholder trust in the private sector. The research outlined the background of the research which highlighted that South Africa's private sector has faced numerous corruption scandals, which have undermined public trust and investor confidence. The background also underscored that whistleblowing, which may be internal or external, is a strategy that has been useful in exposing corruption scandals in many organisations. However, even though there is presence of legal protections enshrined in the constitution, presidential encouragement and mechanisms to encourage whistleblowing, corruption continues to plague the private sector in South Africa. This problem motivated the research to find out about the impact of whistleblowing in reducing corruption, barriers that might be hindering the impact and moral motivation for whistleblowing as well as the impact thereof. To achieve these objectives, the study employed a post-positivist research which provides reality based on socially constructed views around whistleblowing and its impact on reducing corruption within the private sector. The research subsequently utilised a qualitative research approach which provided a suitable approach of exploring issues and understanding underlying reasons and motives in the impact of whistleblowing in reducing corruption within the private sector. A non-probability convenience sampling technique was used to collect purposeful secondary data regarding issues on whistleblowing's impact in the South African private sector. Through thematic content analysis, secondary data collected from court cases, whistle-blower reports, and government reports was analysed to test the study’s propositions. The main themes of this study were structured around barriers, motivations, and impacts. The study’s findings revealed that the deterrence of potential whistleblowers affects the ability of whistleblowing to reduce corruption in the private sector as some cases of corruption are exposed or dealt with due to fear of job loss, harassment or physical harm. The impact of whistleblowing in reducing corruption is lessened by weak legal and managerial safeguards that are supposed to protect whistleblowers. The findings show how the interplay of retaliation, inadequate protections and institutional distrust creates a hostile environment for whistleblowers undermining the whistleblowing’s impact in reducing corruption in the private sector. Leveraging the opportunities presented by these components of ethical conduct, reputational damage and stakeholder trust, there is a potential to improve the impact of whistleblowing in reducing corruption in the private sector. The study discussion also highlighted the critical need for organisations to reform, cultural changes in the corporate environment and legal enforcement that is stronger to support whistleblowing to ensure that it has a positive impact on reducing corruption.
Keywords: Uncatalogued